The Biology and Interplay of Immunotherapy by Leukemia-Oncolytic Virus (iLOV) Immune Responses - Tsang, Jovian (Université d'Ottawa / University of Ottawa, 2015)
Oncolytic viruses (OVs) are novel biological agents that selectively infect and kill malignant cells. OVs can also generate anti-cancer immunity. Our lab exploited this phenomenon and developed an in vitro vaccine with infected leukemia cells with oncolytic virus vaccine – and named immunotherapy by leukemia-oncolytic virus (iLOV) – that provided in vivo protection in a murine model for acute lymphoblastic leukemia. This work further characterizes iLOV biology and the interaction of its immune responses. An in vitro immune response assay was optimized to detect and quantify the in vivo anti-leukemia immunity generated by iLOV. Anti-viral immunity is an obstacle for OV therapy. Although iLOV created anti-viral antibodies towards itself, these neutralizing antibodies did not hinder the vaccine’s ability to initiate complement or dendritic cell activation. We envision personalized versions of iLOV for leukemia patients in remission to prevent the possibility of relapse. This work highlights new advantages for infected cell vaccines and supports the progress of iLOV toward clinical testing.
Keywords: Oncolytic virus; Cancer immunotherapy; Humoral immunity; Immunology; Cancer therapy; Acute lymphoblastic leukemia